Interview Scores Correlate with Fellow Microsurgical Skill and Performance - Schaverien, Mark V.; Butler, Charles E.; Suami, Hiroo; Garvey, Patrick B.; Liu, Jun; Selber, Jesse C. (Journal of Reconstructive Microsurgery, 2018)
Background The interview process for surgical trainees aims to select those individuals who will perform best during training and have the greatest potential as future surgeons. The objective of this study was to evaluate the relationship between criteria assessed at interview, technical skills, and performance, for the first time, to optimize the selection process for a Microsurgery fellowship.Methods Twenty microsurgery fellows in three consecutive annual cohorts at a single academic center were prospectively evaluated. At interview, subjects were scored for multiple standardized domains. At the start and at end of the fellowship, microsurgical technical skill was assessed both in the laboratory and operating room (OR) using a validated assessment tool. At the end of the fellowship, there was a final evaluation of performance.Results At the start, microsurgical skill significantly correlated with almost all domains evaluated at interview, most closely with prior plastic surgery training experience. At the end of the fellowship, skill level improved in all trainees, with the greatest improvement made by the lowest ranked and skilled trainees. The highest ranked trainees, however, made the greatest improvement in speed.Conclusions The results of this study, for the first time, validate the current interview process to correctly select the highest performing and most skilled candidates and support the effectiveness of a 1-year microsurgical fellowship in improving microsurgical skill in all trainees, irrespective of their initial ability. The importance of valuing the relative quality of prior training and experience at selection is also highlighted.
Keywords: fellow; microsurgery; assessment